Effectiveness of Using Teaching Materials Based on a Scientific ApproachEye Civics in School Base - Tanjung, Desy Rahmadani (Journal of General Education Science, 2024)
Citizenship Education (PKn) is a focused subject on formation character inhabitant country which good and responsible answer. Material which the civics subject aims to shape students into individuals who are aware of their rights and obligations, understand national values, and are capable contribute positively to the life of society, nation and state. The aim of this research is to examine the effectiveness of using teaching materials based approach scientific eye lesson Civics in school base. Study using library study methods, relying on books and journals from previous research. Researchers conduct literature and theory studies in each study which is relevant. The research results show that there is a large impact oneffectiveness use material teach based approach scientific eye lesson civicsin school base. Material teach is all information, tool, or writing, which containing organizing material learning in a way systematic, like book text, module, handouts, worksheets, models, mockups, open materials, audio, and interactive resources, can help in planning and review implementation. material teach play important role in the process learning This matter showed from results and discussion every study relatedwhich leads to changes and positive impacts and progress from use these teaching materials in the learning process, especially Civics learning at school base.